Prevalence and associated environmental risk factors of angiostrongylus cantonensis infection in pomacea canaliculata (Golden Apple Snail) in selected Barangays of San Juan, Batangas, Philippines - Garcia, Kim Arielle M. Legaspi, Rowell David G. Macapagat, Maria Ileana L. Molo, Jonica Ruth M. Ople, Joedith G. 4 0 16; 5
ABSTRACT: Ingestion of raw or undercooked Pomace canaliculata, infected with Angiostrongylus cantonensis, could cause human eosinophilic meningitis. Without full awareness into the public health risks, it became a delicacy for Filipinos to make ends meet with the massive economic loss and crop damage. Hence, the study aims to determine the A. cantonensis prevalence in P. canaliculata collected from agricultural areas of selected barangays of San Juan, Batangas, Philippines, and to identify the associated environmental risk factors that increase the likelihood of A. cantonensis acquiring P. canaliculata. A total of 324 snails were randomly collected within 60m x 60m transect lines from the sampling sites. The second (L2) and third larvae (L3) were obtained from the snail through artificial digestion. Results showed that 282 out of 324 snails (87.04%) were infected. It was mostly prevalent in Quipot (89.81%) followed by Talahiban | (88.89%), and Escribano (82.41%), exhibiting no significant difference between the specific prevalence of the three barangays (p>0.05). Statistical analysis also showed no significant difference between the mean intensity of the infection and time of collection; and between the prevalence of infection to the length of the snail host, time of collection, soil parameters, and some water parameters (p>0.05). Whereas the results showed a statistical difference between the mean intensity of infection and length of the snail host; and between the dissolved oxygen (water parameter) and prevalence of A. cantonensis, (p<0.05). Hence, this study calls for collective actions to raise awareness regarding the transmission of A. cantonensis to promote public health. Keywords: Tissue digestion, Dissolved oxygen, Rice fields, Environmental parameters, Invasive
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2